Assistance in the Preparation of the Cikole Village Disaster Risk Reduction Handbook - Damayanti, Verry; Helena Agustina, Ina; Rahminawati, Nan; Mutia Ekasari, Astri; Risang Aji, Riswandha (KnE Social Sciences, 2023)
West Java Province is one of the provinces in Indonesia that is prone to earthquakes. There are three faults that stretch across West Java, namely the Cimandiri Fault, the Lembang Fault, and the Baribis Fault. The Lembang Fault is a geological phenomenon located in the north of the Bandung Basin, stretching from the eastern part of Mount Manglayang to the western part of Parongpong-Csarua through the city of Lembang, for 22 km. The morphology along the Lembang Fault includes active tectonics which can cause large earthquakes in the surrounding area. Among them is Cikole Village, Lembang District. Initial search results show that the people of Cikole Village still have low-disaster risk reduction efforts. Increasing preparedness is one of the important elements of proactive disaster risk reduction activities before a disaster occurs. The priority problem that needs to be addressed through mentoring activities is to increase community preparedness through the preparation of guidelines in the form of a disaster risk reduction handbook. The method used in this activity is community involvement through focus group discussion (FGD). The developed pocketbook measures 7.4 x 10.5 cm and is designed with the dominant color orange. Because orange color denotes alert or ready. The contents of the book include disaster threats in Cikole Village and a guide to disaster preparedness for earthquakes and volcanic eruptions. Keywords: disaster risk reduction, handbook, Sesar Lembang